Fish Diversity as a Biological Indicator of Organic Pollution in the Shatt Al- Basrah canal - Mayada H. Ahmed; Al-Baghdadi , Nada; Majeed, Haider (University of Thi-Qar Journal of agricultural research, 2025)
In addition to being a sewage channel for the entire Basrah Governorate, the Shatt Al-Basrah Canal's environment is polluted by Several things, including spoiled medications, dirt, construction debris, and butchery waste that are dumped into the river and its banks, which results in a low density of organisms and a lack of biodiversity in the area. Two sampling stations were selected, the first station near Al-Zubair Bridge and the second station after the regulator. A total of 1664 fish were captured from Shatt Al-Basrah Canal, which included 14 species belonging to 11 families. The Coptodon zillii fish ranked first in terms of numerical abundance during all the study seasons. Environmental variables (Water temperature, dissolved oxygen, pH, salinity and Biological Oxygen Demand) were measured, Water temperatures ranged from 12 ºC in winter in the second station to 37 ºC in summer in the first station, dissolved oxygen values ranged from 4 mg/L in the summer in the first station to 9 mg/L in winter in the second station, pH values ranged between 7.2 in the spring and 8.3 in the autumn in the first station. Salinity values ranged between 22 g/L in winter and 49.1g/L in summer in the first stations. Biological Oxygen Demand values ranged from 3 mg/L in winter to 5.9 mg/L in summer in the first stations. Both stations recorded a significant increase in the level of organic pollution. With the first station being more affected.